Le concept d'égalité : définition et expérience - Kiss, Charles (Les Cahiers de droit, 1986)
The right to equality is one of the most fundamental of human concepts. The author draws attention to the fact that this right is often depicted in negative terms, usually stating that any form of discrimination is forbidden. The concrete application of equality can sometimes lead to inequalitarian measures. An even policy for equality that is applied to unequal parties can result in a form of inequality. This is the reason why the author endorses equality in fact and not just as a formality in law. According to him, it is indispensable to take positive and specific measures in order to place minorities in a situation of equality and development. These measures, far from being contrary to the principle of non-discrimination, are in conformity with provisions in international treaties pertaining to the right to equality.